Genome-wide association study and functional follow-up identify 14q12 as a candidate risk locus for cervical cancer. Issue 15 (14th February 2022) - Ramachandran, Dhanya; Dennis, Joe; Fachal, Laura; Schürmann, Peter; Bousset, Kristine; Hülse, Fabienne; Mao, Qianqian; Wang, Yingying; Jentschke, Matthias; Böhmer, Gerd; Strauß, Hans-Georg; Hirchenhain, Christine; et al.
Abstract: Cervical cancer is among the leading causes of cancer-related death in females worldwide. Infection by human papillomavirus (HPV) is an established risk factor for cancer development. However, genetic factors contributing to disease risk remain largely unknown. We report on a genome-wide association study (GWAS) on 375 German cervical cancer patients and 866 healthy controls, followed by a replication study comprising 658 patients with invasive cervical cancer, 1361 with cervical dysplasia and 841 healthy controls. Functional validation was performed for the top GWAS variant on chromosome 14q12 (rs225902, close to PRKD1 ). After bioinformatic annotation and in silico predictions, we performed transcript analysis in a cervical tissue series of 317 samples and demonstrate rs225902 as an expression quantitative trait locus (eQTL) for FOXG1 and two tightly co-regulated long non-coding RNAs at this genomic region, CTD - 2251F13 ( lnc-PRKD1-1 ) and CTD - 2503I6 ( lnc-FOXG1-6 ). We also show allele-specific effects of the 14q12 variants via luciferase assays. We propose a combined effect of genotype, HPV status and gene expression at this locus on cervical cancer progression. Taken together, this work uncovers a potential candidate locus with regulatory functions and contributes to the understanding of genetic susceptibility to cervical cancer.